ChemInform Abstract: Combined α, α‐Dialkylprolinol Ether/Broensted Acid Promotes Mannich Reactions of Aldehydes with Unactivated Imines. An Entry to anti‐Configured Propargylic Amino Alcohols. Issue 12 (14th March 2013) - Gomez‐Bengoa, Enrique; Jimenez, Jacqueline; Lapuerta, Irati; Mielgo, Antonia; Oiarbide, Mikel; Otazo, Itziar; Velilla, Irene; Vera, Silvia; Palomo, Claudio
Abstract A series of amino alcohols (III) and (IX) is prepared with 80—98% diastereomeric excess using a hitherto not reported enamine‐mediated antiselective Mannich reaction of corresponding imines with aldehydes (II).